Circulating Monocytes Are Predictive and Responsive in Moderate-to-Severe Plaque Psoriasis Subjects Treated with Apremilast - Larson, Emma L.; DeMeo, Dustin P.; Young, Andrew B.; Margevicius, Seunghee; Rutter, Joseph; Davies, Amanda L.; Rohan, Craig A.; Korman, Neil J.; Travers, Jeffrey B.; McCormick, Thomas S.; Cooper, Kevin D. (Journal of investigative dermatology, 2024)
Monocytes play a critical role in the inflammation associated with psoriasis, and their abnormalities have been reported as biomarkers of cardiovascular event risk, a psoriasis comorbidity. Monocytic cells in chronic inflammatory disorders express elevated levels of cAMP phosphodiesterase. Restoring cAMP levels using the oral cAMP phosphodiesterase-4 inhibitor, apremilast, improves clinical outcomes for a subset of patients with psoriasis. We asked whether aberrant monocyte subsets or transcriptomic pathways can function as biomarkers of psoriasis endotypes that can predict enhanced clinical responses to cAMP phosphodiesterase inhibition. A 16-week open-label study of 22 patients with monocyte flow cytometric and transcriptomic analysis was performed. Subjects with elevated hyperadhesive monocyte doublets at baseline were more likely to be responders to apremilast (P < .0001); 82% of subjects with elevated hyperadhesive monocyte doublets achieved 50% reduction in PASI compared with 46% in those without elevated doublets. We observed a significant reduction in hyperadhesive monocyte-containing doublets and monocyte–platelet aggregates, suggesting an effect of apremilast on the adhesiveness of blood monocytes during chronic inflammation. Monocyte differentially expressed gene transcripts predictive of clinical response uncovered pharmacoendotypes with distinct patterns of nucleotide metabolism, energetics, and differentiation. Further study to understand the basis of drug responsiveness and to develop an apremilast psoriasis treatment algorithm using monocyte-refined gene expression is required to validate and become practical in clinical use, offering patients a test that personalizes their likelihood of clinical response.